Evolution Of the Treatment of Diabetic Retinopathy: From Past to Future - T, Ahmed; A. F, Ikramov; Sh. O, Abdullaev; Kh. Kh, Mamajanov; S.M, Abdullaeva (Journal of Neonatal Surgery, 2025)
This article provides a comprehensive overview of the historical development, current practices, and future directions in the treatment of diabetic retinopathy (DR), a major microvascular complication of diabetes mellitus and a leading cause of vision loss globally. Initially, treatment approaches focused on laser photocoagulation, which helped to stabilize vision but had limited potential for visual improvement and often came with significant side effects. Over time, the introduction of intravitreal pharmacotherapy, particularly anti-VEGF (vascular endothelial growth factor) agents, revolutionized the management of diabetic macular edema and proliferative diabetic retinopathy, offering improved outcomes in preserving and restoring vision. The article also explores the role of corticosteroids, combination therapies, and vitrectomy for advanced cases. Emphasis is placed on recent innovations such as sustained-release drug implants, personalized medicine, and imaging technologies (like OCT and AI-assisted diagnostics) that enhance early detection and monitoring. Looking ahead, the article discusses emerging treatments including gene therapy, regenerative medicine using stem cells, and the potential application of artificial intelligence in predictive analytics and teleophthalmology. By tracing the evolution of therapeutic strategies, the article highlights the significant progress in DR management and underscores the importance of integrating novel biomedical technologies to improve patient outcomes in the future